EFEKTIVITAS PELAKSANAAN SIDANG KELILING DI PENGADILAN AGAMA SANGATTA - Nashirudin, Nashirudin (Ekonomi Syariah STAI Sangatta Kutai Timur, 2022)
In principle the court is waiting for people to come to the story just to settle the case. The court is not looking for a case. However, there are still many people who have difficulty coming to court, even though they really need legal and justice services to fail because they are constrained by geographical, transportation, social and economic conditions. Therefore, it is the duty of the court to provide the best service for them, including during circuit courts.This study aims to determine the implementation of the circuit court at the Sangatta Religious Court and to find out that the implementation of the simple, fast and low cost principle through the circuit court at the Sangatta Religious Court was carried out well. This study aims to determine the effectiveness of the implementation of the circuit court at the Sangatta Religious Court. The results of this study indicate that the mobile court conducted by the Sangatta Religious Court has been fairly effective in terms of providing ease of transportation costs and the distance of travel is expected to be the right solution for justice seekers.